Killer Aquisitions and Beyond: Policy Effects on Innovation Strategies - Armin Schmutzler; Igor Letina; Regina Seibel (ZBW - Leibniz Information Centre for Economics, 2021)
This paper provides a theory of strategic innovation project choice by incumbents and start-ups. We show that prohibiting killer acquisitions strictly reduces the variety of innovation projects. By contrast, we find that prohibiting other acquisitions only has a weakly negative innovation effect, and we provide conditions under which the effect is zero. Furthermore, for both killer and other acquisitions, we identify market conditions under which the innovation effect is small, so that prohibiting acquisitions to enhance competition would be justified.
Keywords: O31; L41; G34; 330; innovation; killer acquisitions; merger policy; potential competition; start-ups